Implementasi Zakat Pengusaha Rumah Makan di Kota Mataram - Marlina Marlina; Busaini Busaini; Muhammad Irwan (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2018)
The purpose of this study is to know the implementation of zakat restaurant entrepreneurs in the city of Mataram. The reason studied, because in the implementation of zakat restaurant entrepreneurs is average of the restaurant entrepreneurs in the city of Mataram already understand what is zakat trade and has channeled it. Based on the above reasons researchers assume that the implementation of zakat restaurant entrepreneurs in the city of Mataram is good because it researchers are eager to know how the implementation of zakat restaurant entrepreneurs in the city of Mataram. This research is conducted with qualitative approach, which process using data collection techniques and analyze the result. The focus of this research is to know the implementation of zakat restaurant entrepreneur in Mataram City. The result of this research about how zakat immigration of restaurant entrepreneurs in Mataram City among others is to go directly and interview the restaurant entrepreneurs in this Mataram City how much zakat that the entrepreneurs of this restaurant give.